Genetic surveillance shows spread of ACT resistance during period of malaria decline in Vietnam (2018-2020) - Kattenberg, Johanna Helena; Mutsaers, Mathijs; Nguyen, Van Hong; Nguyen, Thi Hong Ngoc; Umugwaneza, Arlette; Lara-Escandell, Maria; Nguyen, Xuan Xa; Nguyen, Thi Huong Binh; Rosanas-Urgell, Anna (Frontiers in Genetics, 2024)
IntroductionVietnam’s goal to eliminate malaria by 2030 is challenged by the further spread of drug-resistant Plasmodium falciparum malaria to key antimalarials, particularly dihydroartemisinin-piperaquine (DHA-PPQ).MethodsThe custom targeted NGS amplicon sequencing assay, AmpliSeq Pf Vietnam v2, targeting drug resistance, population genetic- and other markers, was applied to detect genetic diversity and resistance profiles in samples from 8 provinces in Vietnam (n = 354), in a period of steep decline of incidence (2018–2020). Variants in 14 putative resistance genes, including P. falciparum Kelch 13 (PfK13) and P. falciparum chloroquine resistance transporter (Pfcrt), were analyzed and within-country parasite diversity was evaluated. Other targets included KEL1-lineage markers and diagnostic markers of Pfhrp2/3.ResultsA concerning level of DHA-PPQ resistance was detected. The C580Y mutation in PfK13 was found in nearly 80% of recent samples, a significant rise from previous data. Vietnam has experienced a significant challenge with the spread of DHA-PPQ resistant malaria parasites, particularly in the provinces of Binh Phuoc and Gia Lai. Resistance spread to high levels in Binh Thuan prior to the country-wide treatment policy change from DHA-PPQ to pyronadine-artesunate (PA). A complex picture of PPQ-resistance dynamics was observed, with an increase of PPQ-resistance associated Pfcrt mutations, indicating an evolutionary response to antimalarial pressure. Additionally, the compensatory mutation C258W in Pfcrt, which increases chloroquine (CQ) resistance while reversing PPQ resistance, is emerging in Gia Lai following the adoption of PA as the first-line treatment. This study found high levels of multidrug resistance, with over 70% of parasites in 6 out of 8 provinces showing significant sulfadoxine-pyrimethamine (SP) resistance and widespread chloroquine-resistant Pfcrt haplotypes. We also report an absence of P. falciparum histidine rich protein 2 and 3 (Pfhrp2/3) gene deletions, ensuring the continued reliability of HRP2/3-based rapid diagnostic tests. P. falciparum populations in Vietnam are becoming more isolated, with clonal populations showing high geographical clustering by province. The central highlands, particularly Gia Lai province, have the highest residual malaria burden but exhibit low diversity and clonal populations, likely due to the pressures from the antimalarial drugs and targeted national malaria control program (NMCP) efforts.DiscussionIn conclusion, examining a broad panel of full-length resistance genes and SNPs provided high-resolution insights into genetic diversity and resistance evolution in Vietnam, offering valuable information to inform local treatment and intervention strategies.